ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS DAN TINGKAT PENGANGGURAN DI INDONESIA - ME, Zulhanafi; Aimon, Hasdi; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2013)
This study aimed to analyze the influence (1) education and health on labor productivity in Indonesia. (2) productivity, economic growth, investment, government spending, wages and inflation to the unemployment rate in Indonesia. This study uses simultaneous equation model analysis tools with Two Stages Least Squared method (TSLS) from the first quarter of 2000 - the fourth quarter of 2011. The research concludes that (1) health education and significant effect on productivity in Indonesia (2) produktivitias, economic growth, investment, government spending, and wages affect Indonesia's unemployment rate significantly. However, no significant effect on the inflation rate of unemployment in Indonesia. Of research. be advised the government needs to improve the quality of education as well as the budget for public health. The government needs to increase income through employment or investment opening in Indonesia, especially in the real sector Keyword : Productivity, unemployment, education, health, economic growth, investment, government spending, wages and inflation.